Membangun Alternatif Standar Dalam Peningkatan Kualitas Pelayanan Publik - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; DWI WAHYU PRASETYONO (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Public services is one of the citizen’s necessity must have been fulfilled by the government. To do this job getting done, government in the reformation era must change the old paradigm ‘wishing services’ become ‘to provide services’ for citizens, and government must keep better quality for the public services. To increase the quality of public services is purpose to decreasing or terminating the real phenomenon of gap of services in Indonesia’s bureaucracy. Public services in Indonesian’s reformation era must suitable with public service in other countries, it is must be concerned and focused about a standard services principals and the qualities can be measured by using certain defice standards. So that citizens can using public services in many aspects, and to increase their participation to formulate or arranging of public policy or services programs in the future.